Cultural heritage and growth - Jo\~ao Ricardo Faria; Miguel León-Ledesma (University of Kent, Department of Economics, 2003)
In an attempt to measure the impact of cultural heritage on growth, this paper matches the definition of culture as a stock with the cultural heritage list provided by UNESCO, as it is a variable that changes at a very low pace. We test the hypothesis on whether the existence of a strong cultural heritage, that is, where culture has had a large impact on people's life, leads to higher growth. We find evidence that the impact of cultural heritage on growth is positive and it is smaller for countries that either suffer a high degree of political instability or enjoy a high degree of rule of law.
Keywords: D99; O50; Z13; 330; Economic Growth; Social norms; Culture; Kulturgut; Wirtschaftswachstum; Schätzung; Welt; Soziale Norm